Magnetic Resonance Imaging of the Heart is a Robust Method for Diagnosing Myocardial Lesions with Low Availability in Emergency Cardiology Departments - S. K. Kononov; O. V. Solovev (Неотложная медицинская помощь)
This article discusses the problem of underuse, low availability of modern imaging techniques such as magnetic resonance imaging of the heart (MRI). This technique is characterized by high accuracy and uniqueness in the diagnosis of myocardial lesions of various genesis. The widespread introduction of this technique in emergency cardiology departments can improve the accuracy of diagnosis and the effectiveness of patient therapy. Despite the high costs of implementation and current use, modern diagnostic methods can save healthcare resources by reducing hospital stays and improving treatment outcomes.